2018
DOI: 10.4236/tel.2018.814187
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Board Meetings and R&D Investment Strategy: Evidence from OECD Countries

Abstract: This study seeks to examine the impact of frequency of board meetings on R&D investment strategy in OECD countries. The study uses a panel data of 200 companies from Anglo American and European countries between 2010 and 2014. The ordinary least square regression is used to examine the relationships. Additionally, to alleviate the concern of potential endogeneity, we use fixed effect regression, two-stage least squares using instrumental variables. The results show that there is a negative and significant rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…They, therefore, borrow, but the nature of block holders and the fact that they have some control that other shareholders do not have gives them control over management (Tran, 2014). These block holders show that they are reluctant to voluntarily disclose (AlHares et al , 2018a, 2018b, 2018c). This contributes to firms with block holders being seen as riskier, and therefore, as credit risks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They, therefore, borrow, but the nature of block holders and the fact that they have some control that other shareholders do not have gives them control over management (Tran, 2014). These block holders show that they are reluctant to voluntarily disclose (AlHares et al , 2018a, 2018b, 2018c). This contributes to firms with block holders being seen as riskier, and therefore, as credit risks.…”
Section: Methodsmentioning
confidence: 99%
“…According to Tran (2014), blockholders are also founding families that have control over the company, for they are in the position where they could terminate management. Blockholders could also hold information and not disclose it in a timely fashion to shareholders (AlHares et al , 2018a, 2018b, 2018c). Therefore, investors are more likely to see these companies as being risky and so are less likely to invest in these companies.…”
Section: Empirical Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Additionally, more frequent board meetings may not necessarily be useful, because the limited time independent directors spend with the company is not used for the meaningful exchange of ideas among themselves or with the management board (Dash & Raithatha, 2019; Vafeas, 1999). As outsiders, independent directors have less firm‐specific information to make strategic decisions and to monitor management (AlHares et al, 2018; Baldenius et al, 2014; Ji et al, 2019); hence, a higher board meeting frequency may not bring benefits to the firm. Moreover, frequent meetings involve managerial time, higher traveling expenses, administrative support requirements, and directors' meeting fees which may affect other essential or entrepreneurial activities within the firm, as resources are being directed toward less productive activities (Evans et al, 2002; Johl et al, 2015).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…On one hand, both individual board members and past studies have found that more frequent board meetings will lead to better decision making due to the increase in opportunity and time for information processing, consideration, and exchange (Adams & Ferreira, 2012; DeBoskey et al, 2018; Guest, 2019; Hahn & Lasfer, 2016; Jiang et al, 2016; Wahid, 2018). On the other hand, others are of the view that the more frequent the board meetings, the higher the risk of information overload and the compromising of resources and time, thereby resulting in lower efficiency in decision making (AlHares et al, 2018; Jensen, 1993; Ji et al, 2019; Vafeas, 1999). Despite these opposing views, board meetings continue to serve as an important platform for information procurement and exchange between nonindependent (inside) and independent (outside) directors (Brick & Chidambaran, 2010; Hahn & Lasfer, 2016; Ji et al, 2019; Vafeas, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown great interest in the subject of corporate governance (CG) and its possible impact on firms. Consequently, several studies have examined the association between (CG) and firm value (AlHares et al, 2018a;Abdelhak et al, 2019;Gompers et al, 2003;Renders et al, 2010;Kumar & Zattoni, 2013); between (CG) and earnings management (Xie, Davidson, & DaDalt, 2003;AlHares, 2020a); between (CG) and compensation (Kaplan, 2012), and between (CG) and voluntary disclosure (Eng & Mak, 2003;AlHares & Ntim, 2017). However, by contrast, studies examining the extent to which institutional ownership drives cost of capital (COC) are rare.…”
Section: Introductionmentioning
confidence: 99%